Edukasi dan Pemberdayaan Masyarakat dalam Pengelolaan Sampah Rumah Tangga dan Sampah Pesisir di Kelurahan Selumit Pantai Kota Tarakan - Muntiari, Novita Ranti; Fathul Khair Tabri; syamsiah; Muhammad Aris; Muliady; Asma; Lily Herawati (Jurnal Pengabdian Masyarakat - PIMAS, 2026)
Waste management issues remain a significant environmental challenge, particularly in urban and coastal areas, due to population growth, changes in lifestyle, and limitations in effective waste management systems. These conditions contribute to environmental degradation, increased health risks, and threats to coastal ecosystems caused by the accumulation of domestic waste. Selumit Pantai Subdistrict in Tarakan City, as a densely populated coastal area, faces similar problems, which are characterized by low levels of waste segregation and management practices among the community. In response to this condition, the D-IV Health Promotion Study Program of Politeknik Kaltara conducted a community service program through educational and community empowerment approaches in managing household and coastal waste. This activity aimed to enhance community knowledge, awareness, and active participation in implementing environmentally friendly waste management practices. The results indicated an improvement in community understanding and involvement in maintaining environmental cleanliness, which is expected to support the realization of a clean, healthy, and sustainable coastal environment.